The effectiveness of applying project-based and work-integrated learning educational strategies in engineering courses - Mohammadi, Nazanin; Khaksar, Siavash; Ren, Yifei; Murray, Iain (2025)
Engineering educational institutions consistently emphasise incorporating practical learning skills in their curriculum to enhance students' professional knowledge as well as cognitive knowledge. One of the teaching strategies to accomplish this goal is project-based learning (PBL) which promotes opportunities for students to develop solutions for real-world problems. Compared to direct instruction in traditional education, PBL provides opportunities for better student engagement as they are developing a product. Another educational approach that is receiving high attention from curriculum developers in engineering education is Work-integrated learning (WIL). The intended outcome of WIL is to teach students current work environment skills in the field and increase graduates' employability. PURPOSE OR GOAL: In this study, a teaching approach that includes both PBL and WIL was developed to investigate student experience. The model was reviewed to assess the inclusion of professional and cognitive skills in the learning outcomes, as well as the effectiveness of the educational model in improving the graduates' employability. We also evaluated the effectiveness of integrating real- world scenarios into educational programs through WIL and PBL methods and their impact on student learning success. APPROACH OR METHODOLOGY/METHODS: To incorporate real-world projects and learning environments, a collaboration with industry is essential. Therefore, the projects were designed in partnership with external industry stakeholders through Innovation Central Perth (ICP) and academic staff from Curtin University. ICP invites student expressions of interest to participate in finding solutions for industry problems in the form of internships, work experience, and campus-based projects. Successful candidates work directly with external stakeholders and academic mentors to ensure both professional and theoretical learning are incorporated into the project work. ACTUAL OR ANTICIPATED OUTCOMES: The study was conducted from 2021 to 2023. Throughout this two-year period, student learning success, measured through employability metrics, demonstrated a remarkable success rate of 90% employed. The program also shows a high level of satisfaction from companies involved, at 98%. Moreover, there was an increase in industry engagement with the university. CONCLUSIONS/RECOMMENDATIONS/SUMMARY: In conclusion, the ICP project case studies supported the effectiveness of the engineering educational strategies that integrate PBL and WIL. It promotes professional skills, student engagement and autonomy in knowledge construction. The study shows that this educational model improved students' critical thinking, collaboration, teamwork, and problem-solving skills in an authentic learning environment. According to the findings, it also directly contributes to the employability of the graduates